Utilization Of Local Papaya Fruit At Pregnant Women Trimester II On The Quantity Of ASI Association In Kontunaga District, Muna Souteast Sulawesi 2019 - Sutrisna Altahirah (Alma Ata University Press, 2019)
Breast milk is the best nutritional intake for infants in infants 0-24 months. Quantity of ASI (Breast Milk) is needed to meet the needs of the baby which is increasing along with the growth and development of the baby. So from this adequate nutritional needs are needed by pregnant women and prepare to give milk to babies. In the second trimester pregnant women the production of breast milk has begun to be prepared in the mother's body. Lactogagum contained in papaya is very useful and increases milk production. Papaya fruit (carica papaya) is an agricultural commodity that is relatively cheap in price so that it can be reached by people in all walks of life. While the processed products produced from papaya fruit (carica papaya) have a very high economic. Papaya fruit (carica papaya) is included in the category of foods that increase breast milk, because it contains 33% vitamins and 50% more potassium than oranges. Papaya fruit (carica papaya) is good for meeting the needs of potassium during lactation. If the lack of potassium is potentially affected by depression.While the mother's condition must be stable when breastfeeding. This raises the idea of researchers whether local papaya (carica papaya) that grows in Muna Regency can increase the quantity of breast milk. This research was conducted in the kontunaga sub-district divided into two groups namely the intervention group and the control group with a total sample of 50 samples. The research method used is quasi experiment with Independent sample t-test analysis test. The results of this study indicate that there is an effect of giving local papaya to second trimester pregnant women on the quantity of breast milk, this is indicated by the value of P <0.05, which is a very significant effect.